RGD-containing elastin-like polypeptide improves islet transplantation outcomes in diabetic mice. (August 2019) - Lee, Kyeong-Min; Kim, Jung-Hee; Choi, Eun-Sook; Kim, Eunjoo; Choi, Seong-Kyoon; Jeon, Won Bae
Graphical abstract: Abstract: Successful islet transplantation critically depends on the isolation of healthy islets. However, the islet isolation procedure itself contributes to islet death due to the destruction of intra- and peri-islet extracellular matrices (ECMs) during digestion. We investigated whether an R GD-containing e lastin-like p olypeptide (REP) could function as a self-assembling matrix to replenish ECMs and protects islets from cell death. Immediately following isolation, islets were coated with REP coacervate particles via isothermal adsorption of an REP solution followed by thermal gelation. REP-coated islets displayed increased viability and insulin secretory capacity in pretransplant culture compared to untreated islets. Co-transplantation of REP-treated islets and REP beneath the renal sub-capsule in streptozotocin-induced diabetic mice restored normoglycemia and serum insulin levels. Mice that received co-transplants maintained normoglycemia for a longer period of time than those receiving untreated islets without REP. Moreover, co-transplantation sites exhibited enhanced β-cell proliferation and vascularization. Thus, the REP-based coacervation strategy improve the survival, function and therapeutic potential of transplanted islets. Statement of Significance: 1). An artificial matrix polypeptide comprised of thermoresponsive elastin-like peptides and integrin-stimulatory RGD ligands (REP) to reconstitute damaged or lost matrices. 2). Through body temperature-induced coacervation, REP reconstitutes intra-islet environment and enhances islet viability and insulin secretion by activating the pro-survival and insulin signaling pathways. 3). REP-coated islets were transplanted together with the matrix polypeptide under the kidney sub-capsule of mice, it develops a new peri-insular environment, which protects the islet grafts from immune rejection thus extending islet longevity. 4). Our data suggest that in situ self-assembly of biomimetic islet environments become a new platform allowing for improved islet transplantation at extrahepatic sites.